Reports on hospitals and the patient and a domestic workers' charter - Great Britain. Standing Joint Committee of Industrial Women's Organisations ; Labour Party (Great Britain). Advisory Committee on Public Health (London : Labour Party, 1931)
1931 1931 1930s 22 pages cils for domestic workers and employers in every district and a national one as well, just as in other trades. They would plan the conditions, wages and training for their areas. When the Exchanges received notice of a vacancy, it would be registered as under Joint Council conditions or otherwise. Organised domestic workers would only take jobs if Council conditions were given, and so employers would quickly find that it was worth while to give them. Such Councils would require organisation of employers and employed. Such a scheme is not untried. In Birmingham, for some years, mistresses and maids, who were organised by the Workers' Union in a special branch, had such an arrangement. They drew up conditions of employment and rates of wages and both kept their sides of the bargain. Unfortunately this small beginning came to an end, but there is need of a national effort to plan out a scheme of this kind. It should commence with a few districts and gradually extend. If the Ministry of Labour gave it support and took the lead in its administration, if the Exchanges undertook the finding of jobs, if the workers in this industry were placed on the same footing as others in regard to Insurance for Unemployment, and if the Trade Unions backed these efforts, as we are sure they would, we would be able to establish a system which would give freedom and dignity to the domestic worker, do away with the unpopularity of this form of employment and place it in its right position as work of genuine utility and importance. We ask the Conference to adopt this charter and to authorise us to continue our work in making known these proposals and seeking their early adoption. (22) 126/TG/RES/X/1036A/7